Quantification of Abundance of Ammonia Oxidizing Bacteria (AOB) in Palm Oil Plantation Soil - Pramono - (10613008), Wyona
One of the most important steps in the nitrification process in agricultural ecosystems is the ammonium oxidation by ammonium oxidizing bacteria (AOB). In addition, oil palm plantation need a deeper understanding of this group of bacteria in order to improve management and efficiency of fertilizer use. In the past, the ecology and physiology of AOB were difficult to understand because this group of bacteria is difficult to be cultured, but with the qPCR technology, cultivation is not necessary. The purpose of this study is to determine the abundance of AOBs in some oil palm plantation sites and to determine correlated factors that correlated with the abundance. Before quantification was done, the soil was detected in advance of its AOB existance using primers amoA-1F and amoA-2R from Rotthauwe et al. (1997) targeting the amoA gene encoding subunit A of the ammonium monooxygenase enzyme. Detected AOB were suspected to be Nitrosospira bacteria from cluster 3. Quantitative real-time PCR was performed on soil samples from 24 sites in PT AAL plantations and detected bacterial abundance ranging from 10 cells / μL to 107 cells / μL of soil DNA isolates. Of 24 sites, 11 sites did not contain supposedly Nitrosospira cluster 3. The highest bacterial abundance was found in the soil of PT PSKY OB-22, which was 207,533 cells / μL and the lowest bacterial abundance was found on PT MMG OA-10 soil, which was 10.84 cells / μL. Through the principal component analysis (PCA), it is known that sites that didnÃ‚Â’t contain Nitrosospira or have low AOB content have high sand content, low clay content, and relatively low pH. Secondary factors affecting abundance are P and K content. While edaphic factors that are positively correlated positively with large bacterial quantities are clay content, pH, organic N content, and cation exchange capacity. Key words : Ammonium Oxidizing Bacteria, Palm Oil Plantation, qPCR, amoA